PREPARATION OF COOKED SAUSAGE PRODUCTS WITH FOOD FIBERS - RАTSUК, MARIYA; SАRIBЕКОVА, DIANA; VODYANITSKA, ZOYA (Herald of Khmelnytskyi National University. Technical sciences, 2022)
A study of the possibility of adding dietary fiber to cooked sausages is conducted. Analyzing the literature, it was found that the addition of plant fiber to meat products will improve the quality and biological value of finished products by reducing the amount of fat and energy value, improving taste and technological parameters. Dietary fiber leads to the purification of the body from toxins, complete assimilation of food and normalization of the intestinal microflora.Sausages with fiber of wheat, flax, pumpkin and oat fiber were prepared in the work. The main indicators of quality of the received products according to current DSTU 4436: 2005 "Boiled sausages, sausages, sausages, meat loaves" are investigated. It is shown that the addition of plant fibers does not have a negative effect on the organoleptic characteristics of the finished product. It is established that according to the set of organoleptic characteristics it is better to add wheat and pumpkin fiber to the composition of cooked sausages.Physicochemical and microbiological parameters of sausages with the addition of vegetable fibers were determined. It is shown that the content of moisture and fat obtained products meet the standards of current regulations. The protein content in cooked products is slightly lower than regulated by the current DSTU. The total number of microorganisms in cooked meat sausages with vegetable fiber increases slightly compared to DSTU, which may be due to the presence of microflora in the vegetable raw materials that are added.Summarizing the data obtained and taking into account the beneficial properties of turkey meat and fiber, it can be argued that the resulting cooked sausages with the addition of dietary fiber is a functional product that can be recommended to fans of dietary and healthy eating.
Keywords: cooked sausages; meat; functional nutrition; vegetable fiber; sausages